Integrated action planning for biodiversity conservation and sustainable use of highland aquatic resources: evaluating outcomes for the Beijiang River, China - Bunting, S.W.; Luo, S.; Cai, K.; Kundu, N.; Lund, S.; Mishra, R.; Ray, D.; Smith, K.G.; Sugden, Fraser (Informa UK Limited, 2016)
The need for enhanced environmental planning and management for highland aquatic resources is described and a rationale for integrated action planning is presented. Past action planning initiatives for biodiversity conservation and wetland management are reviewed. A re ective account is given of integrated action planning from ve sites in China, India and Vietnam. Eight planning phases are described encompassing: stakeholder assessment and partner selection; rapport building and agreement on collaboration; integrated biodiversity, ecosystem services, livelihoods and policy assessment; problem analysis and target setting; strategic planning; planning and organisation of activities; coordinated implementation and monitoring; evaluation and revised target setting. The scope and targeting of actions are evaluated using the Driving forces, Pressures, State, Impacts and Responses framework and compatibility with biodiversity conservation and socio-economic development objectives are assessed. Criteria to evaluate the quality of planning processes are proposed. Principles for integrated action planning elaborated here should enable stakeholders to formulate plans to reconcile biodiversity conservation with the wise use of wetlands.